PENGARUH MOTIVASI KERJA, DISIPLIN KERJA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PT. CAHAYA KHARISMA PLASINDO - Nugroho, Muhlish Adi; Danarwati, Yanti Sri (FAKULTAS EKONOMI DAN PSIKOLOGI UNWIDHA KLATEN, 2024)
This research aims to determine the influence of work motivation, work discipline and job satisfaction on employee performance at PT. Cahaya Kharisma Plasindo both partially and simultaneously. The research method used in this research is a quantitative approach. The sampling technique used in this research is Non Random Sampling with the Purposive Sampling method. The number of samples studied in this research was 95 respondents, employees of the production department of PT. Cahaya Kharisma Plasindo. The data analysis techniques used in this research are multiple linear regression analysis, t test, f test and coefficient of determination test. The results of this research show that work motivation has a partial effect on employee performance, work discipline has a partial effect on employee performance and job satisfaction has a partial effect on employee performance. These four variables simultaneously have a significant effect on employee performance